PENGARUH LDR, NPL, BOPO, UKURAN PERUSAHAAN, DAN CAR TERHADAP RISIKO KEBANGKRUTAN BANK (Studi pada Bank Umum Konvensional Periode 2012-2014) - Hutasoit, Maria Rosandra Fortunata; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
Corporate banking is an intermediation institution that connects between the surplus and deficit. The function of bank as the intermediary leads bank vulnerable to risk. An increased number of banks that are not in a good position, it is seen from the increasing number of banks with ROA, BOPO, NPL, LDR which is below average. Also there is an inconsistency in the previous studies. This study aims to determine the factors that influence the risk of bank in Indonesia. Based on the bank’s data that is contained in the Financial Services Authority 2012-2014.The population in this study was a conventional commercial bank in Indonesia in 2012-2014. The sampling used purposive sampling with criteria which is listed bank in Financial Services Authority, as well as having an annual report in 2012-2014, and the calculation SDROA to three years back. There are 178 data observations in this study using multiple linear regressions. The variables of this research are the LDR, NPL, ROA, SIZE, and CAR.The results showed that the NPL and ROA have negative effect on the bank's risk. The higher the value of bad loans, the closer the bank to its risks. Higher value of inefficiency, closer the bank to the risk of banking. SIZE showed positive effect on bank's risk. Higher bank’s assets make it closer to the risk. In addition it was found that LDR and CAR did not have significant effect to risk of banking.